The Relevance Of Da'wah Psychology In Q.S. Thaha: 43-44 In The Modern Era - Abdul Khair; Ramadhanita Mustika Sari (ASTEEC, 2024)
The psychology of da'wah as one part of Islamic psychology plays an important role in providing the effectiveness of da'I in spreading Islam. Allah has sent messengers to preach and provide methods that should be emulated by their successors, namely da'i. one of them Q.S. Thaha: 43-44 which tells the story of prophets Musa and Harun who were sent to warn Fir'aun who had exceeded the limit. This article describes the relevance of the psychology of da'wah contained in the verse. This research uses a qualitative method by examining literature reviews and tafsir books that discuss the verse. This research produces a conclusion that the qaulan layyina da'wah method that contains psychological elements is still very relevant in this modern era. This method will also remain relevant over time, because realistically all humans accept peace and reject violence.